VIDEO-ASSISTED THORACOSCOPIC THYMECTOMY IN MYASTHENIA. A NEW APPROACH - V. A. Zhikhаrev; V. A. Porkhаnov; V. A. Koryachkin; Yu. P. Mаlyshev; V. V. Dаnilov (Вестник анестезиологии и реаниматологии, 2018)
The objective of the study: to perform clinical efficiency assessment of epidural anesthesia combined with an epiglottic airway and auxiliary pulmonary ventilation in video-assisted thoracoscopic thymectomies.Subjects and methods. 9 patients with generalized myasthenia who had video-assisted thoracoscopic thymectomy were examined.Results. The efficient level of analgesia during surgery was confirmed clinically: patients were dry, pink, warm, the diuresis rate made 60 ml/h. Upon the completion of surgery, the patients were recovered in 1-2 minutes on the average. At the same time, the epiglottic airway was removed. The patients were able to walk in the ward without any assistance in 1 hour after surgery. In the post-operative period, on the average, the pain intensity made 1.50 ± 0.87 scores as per VAS. None of the patients needed therapeutic fibrobronchoscopy. No intra-operative or post-operative complications were registered. All 9 patients were transferred to the relevant specialized ward on the day of surgery; 6 (66.7%) went home on the 5th day after surgery, and 3 (33.3%) – on the 6th day.Conclusion. Epidural block combined with an epiglottic airway and auxiliary pulmonary ventilation without tracheal intubation and muscle relaxants in video-assisted thoracoscopic thymectomies is an effective and safe method.